Assessment of progression of COPD: report of a workshop held in Leuven, 11–12 March 2004. Issue 4 (24th March 2005) - Decramer, M; Gosselink, R; Rutten-Van Mölken, M; Buffels, J; Van Schayck, O; Gevenois, P-A; Pellegrino, R; Derom, E; De Backer, W
Abstract : Recently performed long term trials have enhanced the insight into the assessment of progression of COPD. The present review focuses on the initial assessment of COPD in general practice and the assessment of disease progression. Several variables may be used to assess this progression, all of which are associated with significant methodological problems. Finding the appropriate mix of outcome measures to capture all aspects of disease progression is a significant challenge.